Double Opposing Zplasty with VY Advancement of the perineum: Long-term results of a new technique as an alternative to Fenton's operation for narrowing and splitting of the skin at the posterior vaginal fourchette. (April 2018) - Frappell, Jonathan; Riadin, Lia; Ebeid, Elhami; Asmussen, Tilo; Morris, Robert
Abstract: Objective: To assess the long-term results of our experience with this technique which we have developed as an alternative to Fenton's procedure. Study design: A retrospective questionnaire study of all patients undergoing the procedure in our department from Jan. 2006 to Dec. 2013. The main outcome measure was the change in sexual satisfaction scores, using a visual analogue scale, before and after the procedure. Results: There was a statistically significant improvement in sexual satisfaction scores in the majority of patients. This was particularly marked in patients who had previously undergone an unsuccessful Fenton's operation. Conclusions: Double opposing Z plasty with VY advancement of the perineum (The Plymouth Procedure)should be offered to all patients in whom Fenton's operation has been unsuccessful, and considered as an alternative to Fenton's as a primary procedure.